Evaluating geometric quality and accuracy of 3D building models: a concept of 3D model evaluation method - Klapa, Przemysław (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Evaluation of 3D building model quality is central to civil engineering, geodesy, architecture and the construction industry as it facilitates the assessment of the model’s accuracy, completeness and interoperability. The article presents a concept of a versatile method for evaluating the quality of 3D building models, the 3D model evaluation method. It can compare models regardless of their data sources, modelling techniques, visualization and file format. The method covers key quality aspects such as completeness, which reflects the degree to which object components are represented; accuracy, which concerns geometric and positioning integrity; and interoperability, which includes the model’s compliance with standards, editability and reusability. The author investigated a range of 3D modelling approaches, including mesh, solid and parametric models derived from a variety of data sources. The proposed evaluation method is founded on analyzing model attribute values for selected criteria followed by visualization of these values on a radar chart. The model quality index, normalized to [0; 1], quantifies the 3D model quality. The results demonstrate the method’s effectiveness for 3D model evaluation regarding both geometric and non-geometric aspects. The method can be applied in GIS, BIM, spatial analyses, civil engineering and environmental engineering. It provides a single pipeline for classifying and comparing different types of models. The 3D model evaluation method provides a universal, structured and practical basis for comparing 3D models across sources and techniques, ensuring result comparability and consistent quality reporting.